Parâmetros e correlações genéticas e fenotípicas para peso e medidas morfométricas em rainhas Apis mellifera africanizadas - Halak, André Luiz (2012)
This research was carried out to estimate genetic and phenotypic parameters for weight, length and abdomen width of newly emerged Africanized queens, checking between the morphometric characteristics and weight whether they can be used as selection criteria. It was collected 60 colonies randomly, and set out in experimental field. It was used the predictions of software Multiple Trait Gibbs Sampling in Animal Models - MTGSAM, to select the newly emerged queens with better genetic values for three generations. The parameter estimates were obtained using the software R. Values of weight, width and length of the abdomen were analyzed by ANOVA and Tukey?s test at 5% significance. Data from genetic and phenotypic correlations were estimated by Pearson?s correlation coefficient and validated by ?t? test. The weight characteristic showed an average of 215.64 mg for queens at emerges, and length and abdomen width, an average of 11.65 mm and 5.09 mm, respectively. Significant differences in mean values of weight and length of abdomen were observed between the three generations. The values of heritability for weight (W), length (AL) and abdomen width (AW), were 0.29, 0.15 and 0.35 by unicharacter analysis, while the tricharacter analysis presented values of 0.40, 0.23 and 0.25, respectively. The means of genetic and phenotypic (co)variance obtained by bicharacter analysis were positive. The WxAL interaction presented additive genetic (co)variance of 2.48 and phenotypic of 0.82. Values of 1.53 and 0.17, respectively, were found for additive genetic and phenotypic (co)variance for n WxAW interaction and finally, the ALxAW interaction with values of 0.07 and 0.18 for additive genetic and phenotypic (co)variance, respectively. The additive genetic (co)variance by tricharacter analysis for WxAL interaction was 2.82, for ALxAW interaction was 0.03 and 1.29 for WxAW interaction, while the (co)variance phenotypic for tricharacter analysis of WxAL interaction was 7.21; WxAW - was 1.72 and 0.06 was for ALxAW. The genetic correlation by the bicharacter analysis varied from 0.86 to 0.94, while the tricharacter analysis showed lower values ranging from 0.20 to 0.41. The phenotypic correlation by bicharacter analysis presented low values, ranging from 0.01 to 0.07, while the tricharacter analysis presented higher values from 0.24 to 0.57. The parameters weight, length and abdomen width can be used as selection criteria in breeding programs. Estimated values by tricharacter analysis are more accurated when compared to values estimated by further analysis.